2022
DOI: 10.1039/d1se01080h
|View full text |Cite
|
Sign up to set email alerts
|

High surface area MnO2nanomaterials synthesized by selective cation dissolution for efficient water oxidation

Abstract: Artificial photosynthesis is a promising method that directly transforms solar energy into chemical energy. To achieve artificial photosynthesis, efficient water oxidation catalysts (WOCs) are essential. In nature, the manganese-oxo-calcium cluster...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 64 publications
0
7
0
Order By: Relevance
“…8–10 Consequently, it is tremendously desirable to prepare high-efficiency and low-cost bifunctional catalysts for overall water splitting. 11,12…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…8–10 Consequently, it is tremendously desirable to prepare high-efficiency and low-cost bifunctional catalysts for overall water splitting. 11,12…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10] Consequently, it is tremendously desirable to prepare high-efficiency and low-cost bifunctional catalysts for overall water splitting. 11,12 Recently, various investigations have shown that MoS 2 is a promising candidate for the HER. [13][14][15][16] However, MoS 2 also has drawbacks such as covering of active sites, poor conductivity, and low OER performance.…”
Section: Introductionmentioning
confidence: 99%
“…Some research groups investigated the effects of other ions on layered Mn oxide to investigate its structure or catalytic activity. These effects include inducing Mn­(III), modifying the chemical and electronical properties of layered Mn oxide, enhancing charge mobility, and tuning the electronic structure. …”
Section: Introductionmentioning
confidence: 99%
“…4 It involves two reaction steps: a hydrogen evolution reaction (HER) and an oxygen evolution reaction (OER). [5][6][7] However, an anodic oxygen evolution reaction involves the transfer of four electrons, 8 and the reaction kinetics is very slow. Due to the inevitable overpotential generated by the two electrodes, the cell voltage of electrolytic water far exceeds the theoretical voltage of 1.23 V, which is unfavorable for energy saving hydrogen production.…”
Section: Introductionmentioning
confidence: 99%
“…Wu's team achieved gradient optimization of the electronic spin state of the material through stress action. 35 The change of Co 3+ from a low spin state (LS T 6 2g e 0 g ) to an intermediate spin state (IS T 5 2g e 1 g ) is induced by stress, and the change of the spin state leads to the change of the e g electron filling state, electrical conductivity and reaction adsorption free energy, thus adjusting the catalytic performance of the OER. Gao et al successfully prepared a 3D NiFe LDH microtubule structure rich in oxygen defects.…”
Section: Introductionmentioning
confidence: 99%